The Impact Of Liquidity And Solvency On Profitability In Food And Beverage Companies Listed On The Indonesian Stock Exchange From 2018 To 2022 - Nagita Wulandari; Triya Vebrianty; Raudatul Jannah; Dwi Saraswati (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the effect of liquidity and solvency on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. Liquidity is measured using the current ratio which describes the company's ability to meet its short-term obligations, while solvency is measured using the Debt to Equity Ratio (DER) which reflects the balance between debt and capital owned by the company in financing its assets. Profitability is measured using the Return on Assets (ROA) ratio which shows the company's ability to generate profits from the total assets owned by the company. The participants in this study were food and beverage companies, with research samples including INDF, ICBP, MYOR, ULTJ, and GOOD companies. The sampling method used is purposive sampling. The analysis method used is simple linear regression analysis to test the effect between the independent variable and the dependent variable. The results showed that, individually, liquidity has no significant effect on profitability, as well as solvency has no influence individually on profitability